Human rights, indian financial system, communication skills (FC-II) SYBSC - Basantani K.T., Doctor Aspi H., Deshmukh M.S. (Sheth publishers,Mumbai, 2008)
Personality Development
ENGLISH
Keywords: Human rights, indian financial system, communication skills (FC-II) SYBSC; Personality Development; Personality Development